Indeks Literasi Zakat Pada Mahasiswa Program Studi Manajemen Zakat Dan Wakaf - Mail Hilian Batin; Muhammad Habibi; Iceu Sri Gustiana (Jurnal I-Philanthropy, 2022)
This study aims to measure the level of understanding of students of the zakat and waqf management study program, Faculty of Islamic Economics and Business UIN Raden Fatah Palembang by using a survey research method with a descriptive approach. This research is focused on measuring the level of understanding and literacy of zakat and waqf management study program students regarding zakat objects by involving 90 students from 4 lecture batches namely class of 2018, class of 2019, class of 2020 and class of 2021. Student literacy and understanding of the factors that determine the role of zakat students to educate the public to fulfill zakat obligations. The results of this study provide the level of understanding and literacy of the study program from each lecture. The results of the research show that the zakat literacy index for students of the zakat and waqf management study program obtained a score of 83.12% which is included in the high category. Students of the 2019 college class are the highest generation in understanding and literacy regarding zakat with the acquisition of a zakat literacy index of 87.55%.